WILD PTERIDOPHYTA THAT CAN BE USED AS DECORATIVE PLANTS BY THE SOCIALITY - Nursyahra, Nursyahra; Putri, Lola Dwi; Zural, Mimin Mardhiah; Meriko, Lince (Jurnal Bioconcetta, 2021)
Abstract. Fern is a plant that is spread so widely that it can be found from the lowlands to the highlands, has a high diversity of Indonesian flora groups and many grow in moist areas such as oil palm plantations, forests, hills and even river flows. In the river there are fern plants that grow attached to the stone. The study was conducted in July-August 2019 and aims to find out the types of fern plants that are used as decorative plants by sociality. The method used in this study is a descriptive survey by field observation and direct collection. Collections obtained were identified using with plant taxonomy books and field guides. Analysis of research data was done descriptively. The results showed that there were 6 types of decorative fern plants consisting of 1 class, 1 nation, 5 tribes, and 6 clans.Keywords:Â Pteridophyta, The Benefits of Fern